CD40 gene polymorphism and its expression in children with Kawasaki disease from North India: a preliminary case–control study and meta-analysis - Patra, Pratap Kumar; Jindal, Ankur Kumar; Rikhi, Rashmi; Kaur, Anit; Srivastava, Priyanka; Suri, Deepti; Rawat, Amit; Pilania, Rakesh; Singh, Surjit (Frontiers in Pediatrics, 2023)
Introduction CD40 gene single-nucleotide polymorphisms (SNPs) have been associated with susceptibility and development of coronary artery abnormalities (CAAs) in children with Kawasaki disease (KD) in Japanese, Chinese, and Taiwanese populations. However, data on SNPs of the CD40 gene in patients with KD from the Indian subcontinent are not available. We studied the CD40 gene polymorphisms and its expression in children with KD from North India. Methods SNPs of the CD40 gene (rs4810485, rs1535045) were studied using Sanger sequencing. CD40 expression was studied by flow cytometry. Meta-analysis was carried out to assess the role of both SNPs of the CD40 gene in KD. GRADEpro GDT software (v.3.2) was used to assess the “certainty of evidence.” Results Forty-one patients with KD and 41 age-, sex-matched febrile controls were enrolled. However, none of the alleles and genotypes of the CD40 gene were found to be associated with KD. CD40 expression was higher in KD and in KD with CAAs compared to controls, but it failed to reach statistical significance. In a meta-analysis, the T allele of rs153045 was found to be significantly associated with KD (OR = 1.28; 95% confidence interval (: 1.09–1.50; p = 0.002). The GRADE of evidence for this outcome, however, is of “ very low certainty.” Conclusion The present study found no association between SNPs (rs4810485 and rs153045) and susceptibility to KD. This could be a reflection of a modest sample size. CD40 expression was higher in KD and in KD with CAAs. In the meta-analysis, the T allele of rs153045 was significantly associated with KD. Our study confirms a significant genetic heterogeneity in KD among different ethnicities.